2013
DOI: 10.1002/ange.201301974
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of an Adsorbed Phospholipid Monolayer Submitted to Prolonged Periodical Surface Density Variations

Abstract: The adsorption of phospholipids at interfaces determines many biological phenomena, from cell life to lung-surfactant dynamics. The lung surfactant reduces the surface tension in the alveoli and ensures normal breathing. Although the dynamic adsorption and interfacial rheology of dipalmitoylphosphatidylcholine (DPPC), the main component of the native lung surfactant, has been extensively investigated to understand the mechanism of respiration, [1][2][3][4][5][6][7][8] this quest has met some serious difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…As summarized in Table 1, DPPC vesicles both adsorbed and spread onto the air-water surface result in an equilibrium surface tension of 41 mN/m at 37 C. This value is close to that obtained with the micropipette technique (28) but significantly lower than that obtained with various bubble methods (26,27). Nevertheless, it is found that only the DPPC monolayer spread from organic solvent is able to reach the intrinsic equilibrium surface tension of the phospholipid monolayer (i.e., $22 mN/m).…”
Section: Experimental Measurements Of the Surface Tension And Morphology Of Dppc Filmssupporting
confidence: 79%
See 2 more Smart Citations
“…As summarized in Table 1, DPPC vesicles both adsorbed and spread onto the air-water surface result in an equilibrium surface tension of 41 mN/m at 37 C. This value is close to that obtained with the micropipette technique (28) but significantly lower than that obtained with various bubble methods (26,27). Nevertheless, it is found that only the DPPC monolayer spread from organic solvent is able to reach the intrinsic equilibrium surface tension of the phospholipid monolayer (i.e., $22 mN/m).…”
Section: Experimental Measurements Of the Surface Tension And Morphology Of Dppc Filmssupporting
confidence: 79%
“…The dynamic surface tension measurements showed significant discrepancies with different preparations of DPPC vesicles (25,29,30). Many measured equilibrium surface tensions were much higher than the theoretical equilibrium surface tension of the air-alkyl surface (21,(24)(25)(26)(28)(29)(30)(31). Infrared reflection-absorption spectroscopy results showed that there were more than one monolayer at the air-water surface after adsorption of the DPPC vesicles (25,29,30).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of sub-millimeter-sized microbubbles shelled with phospholipids, molecular adsorption to the gas−liquid interface can be evaluated by bubble profile analysis tensiometry. 36 Here, we investigated the adsorption and desorption characteristics of DMPC from single bubbles, tens of micrometers in size, using an instrument based on an ultrasound transducer and a high-speed camera. The phospholipid, 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), was purchased from NOF Corporation [CAS Registry No.…”
Section: Methodsmentioning
confidence: 99%
“…The microscopic structure of the shell of a bubble and its rheology are the essential factors that determine bubble vibrational characteristics. A monolayer film of amphiphilic molecules is usually formed at the gas/liquid interface on the bubble surface. Although the vibration amplitude of microbubbles coated with phospholipids or other surfactants under sonication is restrained by the viscoelasticity of the shell, the molecular film prevents the diffusion of the internal gas. Kabalnov et al , investigated the lifetime of fluorocarbon-stabilized phospholipid-coated microbubbles in the bloodstream theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%